Perencanaan Model Bisnis Konsultan Arsitektur Lanskap di Lagom Landscape Desain - Amelia Utami Geraldine Mandagi; Harianto Harianto; Siti Jahroh (http://arl.faperta.ipb.ac.id/, 2023)
The Covid-19 pandemic affected the economy which resulted in the decline of construction work. This affected Lagom Landscape Design (LLD) business practices. This research aims to formulate a new business model which can be used as a business model of Lagom Landscape Design in the future. This descriptive qualitative research used purposive sampling as the technique of determining respondents, based on the Business Model Canvas (BMC) approach, which was equipped with SWOT analysis and Blue Ocean Strategy (BOS). New business model using BMC is determined in consideration of the market segment and key activities as the key factors. The result of the research indicates that the customer segment of LLD has changed to private sectors, developers, hospitality business and government projects. LLD need to reach a wider range of customers by diversifying its key activities to increase the revenue strams and create a brand image and awareness. The empirical result of this study is to contribute ideas for broadening the insights about the business development strategy of landscape architecture consultant.